2014
DOI: 10.1155/2014/905639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the In Vitro Antiplasmodial, Antileishmanial, and Antitrypanosomal Activity of Medicinal Plants Used in Saudi and Yemeni Traditional Medicine

Abstract: The antiplasmodial, antileishmanial, and antitrypanosomal activity of twenty-five medicinal plants distributed in Saudi Arabia and Yemen was evaluated. The plants were extracted with methanol and screened in vitro against erythrocytic schizonts of Plasmodium falciparum, intracellular amastigotes of Leishmania infantum and Trypanosoma cruzi, and free trypomastigotes of T. brucei. To assess selectivity, cytotoxicity was determined on MRC-5 cells. Criteria for activity were an IC50 < 10 μg/mL and high selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…in Brazil (França et al ., ), Brunfelsia grandiflora D. Don, Cestrum racemosum Ruiz & Pav., Nicotiana tabacum L., Solanum mammosum L. and Solanum nigrum L. in Ecuador (Gachet et al ., ) and Solanum peruvianum L. in Peru (Valadeau et al ., ). Pharmacological activity of B. grandiflora D. Don (Fuchino et al ., ), Datura stramonium L. (Nikmehr et al ., ), Physalis angulata L. (Guimarães et al ., ), Solanum glabratum Dunal (Mothana et al ., ) and Solanum torvum Sw. (Hubert et al ., ) against different Leishmania sp. has been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in Brazil (França et al ., ), Brunfelsia grandiflora D. Don, Cestrum racemosum Ruiz & Pav., Nicotiana tabacum L., Solanum mammosum L. and Solanum nigrum L. in Ecuador (Gachet et al ., ) and Solanum peruvianum L. in Peru (Valadeau et al ., ). Pharmacological activity of B. grandiflora D. Don (Fuchino et al ., ), Datura stramonium L. (Nikmehr et al ., ), Physalis angulata L. (Guimarães et al ., ), Solanum glabratum Dunal (Mothana et al ., ) and Solanum torvum Sw. (Hubert et al ., ) against different Leishmania sp. has been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…However, until now, there is no report on antileishmanial activity of solanaceous plants from Cuba. Different species of this family have been reported to have ethnomedicinal uses against leishmaniasis (França et al ., ; Valadeau et al ., ; Gachet et al ., ), and experimental pharmacological activities against Leishmania have been reported (Fuchino et al ., ; Guimarães et al ., ; Hubert et al ., ; Mothana et al ., ; Nikmehr et al ., ). Therefore, we have performed an in vitro antileishmanial assessment of plants growing in Cuba belonging to Solanaceae family.…”
Section: Introductionmentioning
confidence: 98%
“…Hypoestenonols A (12) and B (13), hypoestenone (15), and verticillarone (14) were isolated from the MeOH extract of the aerial parts of Hypoestes forskalei. The MeOH extract showed antimalarial potential against Plasmodium falciparum K 1-strain with half maximal inhibitory concentration (IC 50 ) 8.8 µg/mL, compared to chloroquine (IC 50 ) 0.3 μM).…”
Section: Biological Activities Hypoestes Forskaleimentioning
confidence: 99%
“…They reported that some species form the Lamiaceae family have anti-leishmanial effects (12). In mahmoudvand's study, in vitro anti-leishmanial activity of different extracts of B. vulgaris against promastigote and amastigote of L. tropica and L. infantum was assessed in a murine macrophage model.…”
Section: In Vitro Study Of Herbal Drugsmentioning
confidence: 99%